2016
DOI: 10.2139/ssrn.2800101
|View full text |Cite
|
Sign up to set email alerts
|

Does Internal and External Research and Development Affect Innovation of Small and Medium-Sized Enterprises? Evidence from India and Pakistan

Abstract: The views expressed in this paper are the views of the author and do not necessarily reflect the views or policies of ADBI, ADB, its Board of Directors, or the governments they represent. ADBI does not guarantee the accuracy of the data included in this paper and accepts no responsibility for any consequences of their use. Terminology used may not necessarily be consistent with ADB official terms. Working papers are subject to formal revision and correction before they are finalized and considered published. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Research and development added to the on-the-job training would enhance the absorption capacity and stock of knowledge of the enterprises that would induce innovation of the enterprises. The findings of Rehman (2016) conducted in India and those of Abdu and Jibir (2017) in Nigeria corroborate this finding. The study support that R & D has a positive impact on the product and process innovation.…”
Section: Innovation In All-sized Enterprisessupporting
confidence: 69%
“…Research and development added to the on-the-job training would enhance the absorption capacity and stock of knowledge of the enterprises that would induce innovation of the enterprises. The findings of Rehman (2016) conducted in India and those of Abdu and Jibir (2017) in Nigeria corroborate this finding. The study support that R & D has a positive impact on the product and process innovation.…”
Section: Innovation In All-sized Enterprisessupporting
confidence: 69%
“…Bad macroeconomic policies are identified as prime reasons of ineffectiveness of aid in Pakistan (Khan & Ahmed, 2007;Muhammad & Qayyum, 2011). Another possible reason of these results is the weak NIS and low absorptive capacity of Pakistan (Rehman, 2016;Speakman et al, 2012;Zaman, 2018) because scholars reported that weak NIS and absorptive capacity would lower the effectiveness of aid (Feeny & de Silva, 2012).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The study of previous research contributions shows a wide coverage of studies. In the Indian context, several industries have been covered which include pharmaceutical (Kumar & Saqib, 1996;Mishra, 2011); manufacturing (Pradeep et al, 2017;Jaisinghani, 2016;Joseph, 2011;Naik et al, 2012;Parameswaran, 2010;Pradhan, 2011;Sharma, 2011), and small and medium enterprises (Rehman, 2016). In the context of Asia, there are studies in Pakistan (Ghaffar & Khan, 2014), Jordan (Freihat & Kanakriyah, 2017), China (Wang, 2011;Zhu & Huang, 2012), Japan (Rao et al, 2013), Taiwan (Hsu et al, 2013) and Iran Khajavi & Sadeghnia, 2016).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…An interesting study by Pradeep et al (2017) finds a spill over effect of investment in R&D on the productivity levels of foreign and Indian manufacturing firms. Rehman (2016) in a cross-country study identifies the positive influence of internal and external R&D expenditures on both product and process innovation. The study by Purkayastha et al (2018) draws a connection between the levels of R&D expenditure and internationalisation.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%